Hyperbaric Oxygen Exposures for Intrahepatic Abscesses Produced in Mice by Nonsporeforming Anaerobic Bacteria - Hill, Gale B. (1976)
Hyperbaric oxygen exposures were evaluated for treatment of progressive liver abscesses produced by intraperitoneal injection of combined cultures of Fusobacterium necrophorum plus either Bacteroides fragilis subsp. fragilis or Fusobacterium nucleatum in a mouse model. Infected control and hyperbaric oxygen-exposed mice were autopsied 5 or 6 weeks after inoculation of bacteria and were assigned numerical pathology scores according to the number and size of abscesses present. Seventeen daily 3-h exposures to 100% O(2) at 2 atmospheres absolute pressure begun either 1 day or 1 week after injection of bacteria significantly reduced the number and size of abscesses among mice infected with either mixture of anaerobic organisms. Abscesses due to mixed fusobacteria were often completely resolved. These data support the efficacy of hyperbaric oxygen for treatment of mixed anaerobic infection produced by Bacteroides and Fusobacterium species and suggest its further evaluation as a potential alternate or adjunct to present therapy for certain types of serious anaerobic infection.